2020
DOI: 10.1038/s41467-020-19883-7
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 genomic and subgenomic RNAs in diagnostic samples are not an indicator of active replication

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) was first detected in late December 2019 and has spread worldwide. Coronaviruses are enveloped, positive sense, single-stranded RNA viruses and employ a complicated pattern of virus genome length RNA replication as well as transcription of genome length and leader containing subgenomic RNAs. Although not fully understood, both replication and transcription are thought to take place in so-called double-membrane vesicles in the cytoplasm of infected ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
251
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(272 citation statements)
references
References 44 publications
20
251
1
Order By: Relevance
“…The detection of these subgenomic RNAs in our clinical nasopharyngeal swabs confirms that these transcripts are moderately stable, being the sgN RNA mainly associated to the highest viral load. Moreover, in contrast to the data reported by Alexandersen et al [17], who reported that the relative abundance of subgenomic RNAs may be more related to the sample's quality and storage before the laboratory assay than to the actual stage of infection, we can emphasize that the persistence of sgN RNAs might be considered as a candidate biomarker of the active viral load, regardless of the pre-analytical conditions and analytical diagnostic kit. It is noteworthy that sgN was reported as the most expressed transcript in other sample types, like stool [19]; the authors of this research concluded that the detection of sgN and sgE improves the diagnosis of COVID-19, particularly in patients who are suspected of being infected but with negative results in the upper respiratory tract.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The detection of these subgenomic RNAs in our clinical nasopharyngeal swabs confirms that these transcripts are moderately stable, being the sgN RNA mainly associated to the highest viral load. Moreover, in contrast to the data reported by Alexandersen et al [17], who reported that the relative abundance of subgenomic RNAs may be more related to the sample's quality and storage before the laboratory assay than to the actual stage of infection, we can emphasize that the persistence of sgN RNAs might be considered as a candidate biomarker of the active viral load, regardless of the pre-analytical conditions and analytical diagnostic kit. It is noteworthy that sgN was reported as the most expressed transcript in other sample types, like stool [19]; the authors of this research concluded that the detection of sgN and sgE improves the diagnosis of COVID-19, particularly in patients who are suspected of being infected but with negative results in the upper respiratory tract.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to both the preanalytical and analytical variables [5,16] affecting the virus detection in oronasopharyngeal swabs, we used different methods in order to better evaluate the expression of the subgenomic transcripts in relationship to the genomic transcripts. The high-sensitivity PCR-based tests are nearly 100% accurate in identifying infected people, if they are administered appropriately [1,17]. In order to avoid biases related to the amplification process of RNA from unknown swabs, we evaluated the analytical performance of the five kits reported herein using both negative sample swabs and phosphate buffer medium, into which genomic constructs of gene N and E were spikedin at different dilutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is the poorly understood process of SARS-CoV-2 viral replication which involves viral proteins and RNA being sequestered in double-membrane vesicles in the cytoplasm and extensive remodeling of intracellular membrane systems (29). Such vesicles have been shown to be nuclease resistant and may persist intracellularly after active viral infection (30). This RNA would then ultimately get released upon cell death and hence the differential presence of remnant viral RNA between the nasopharynx and the anterior nares/oral cavity can be explained by the reduced percentage of vulnerable ACE2 expressing cells in these locations (31), the significantly slower rate of epithelial cell turnover in the nasopharyngeal mucosa compared to the buccal or anterior nasal mucosa as well as the greater abrasive forces applied to the epithelium during collection of a nasopharyngeal swab than an anterior nares or oral fluid swab which are likely to release more intracellular material.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…To identify active virus replication, authors of this study and a few subsequent studies have used subgenomic RNA as evidence of active infection 30 33 . However, two very recent studies have found that SARS-CoV-2 subgenomic RNA has a prolonged life in respiratory samples after the onset of symptoms 34 , 35 , therefore, may not be a proper indictor of active coronavirus replication 34 . Regardless, high viral RNA loads (> 10 6 copies per sample) determined by real-time RT-PCR have been confirmed to be associated with shedding of infectious virus prior to seroconversion in patients with symptoms ranging from mild to severe or critical 30 , 35 .…”
Section: Discussionmentioning
confidence: 99%